2019
DOI: 10.1016/j.bbalip.2019.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Effect of liver fatty acid binding protein (L-FABP) gene ablation on lipid metabolism in high glucose diet (HGD) pair-fed mice

Abstract: Liver fatty acid binding protein (L-FABP) is the major fatty acid binding/"chaperone" protein in hepatic cytosol. Although fatty acids can be derived from the breakdown of dietary fat and glucose, relatively little is known regarding the impact of L-FABP on phenotype in the context of high dietary glucose. Potential impact was examined in wild-type (WT) and Lfabp gene ablated (LKO) female mice fed either a control or pair-fed high glucose diet (HGD). WT mice fed HGD alone exhibited decreased whole body weight … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 84 publications
0
4
0
Order By: Relevance
“…L‐FABP, apoB and mtp are gens related to the transportation of lipid. L‐FABP is the protein that major in promoting uptake and transport in liver cytoplasm (McIntosh et al, 2019). The mtp gene is responsible for packaging TG in the transportation of lipid (Schlegel & Stainier, 2006), while apoB was proved to essential for the hepatic assemble and secretion of TG (Storch & Thumser, 2010; Yan et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…L‐FABP, apoB and mtp are gens related to the transportation of lipid. L‐FABP is the protein that major in promoting uptake and transport in liver cytoplasm (McIntosh et al, 2019). The mtp gene is responsible for packaging TG in the transportation of lipid (Schlegel & Stainier, 2006), while apoB was proved to essential for the hepatic assemble and secretion of TG (Storch & Thumser, 2010; Yan et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…It is mainly responsible for lipid metabolism, including fatty acid uptake, trafficking, and lipid storage [48]. Studies have previously shown that FABP1 mainly transports fatty acids to the liver and converts them into TG and phospholipids, thereby participating in intracellular fatty acid homeostasis [49,50], or directly interacts with fatty acyl-CoA synthases to donate bound long-chain fatty acids (LCFAs) for conversion to LCFA-CoAs, thereby enhancing the uptake of LCFA and cholesterol in living cells and promoting fat storage in the liver [49,51,52]. Therefore, FABP1 plays a critical role in regulating the metabolism underlying hepatic steatosis.…”
Section: Discussionmentioning
confidence: 99%
“…According to previous studies, the enhancement of the activity of PPARα and PPARγ in tissues can regulate fat metabolism and reduce the accumulation of fat in tissues ( Lee et al, 2012 ; Gu et al, 2015 ). Extensive research indicates that by increasing the expression of downstream target genes in the PPAR pathway, lipid metabolism processes can be regulated, such as converting cholesterol metabolism to synthesize bile acids, fatty acid transport to regulate fat deposition, and fatty acid oxidation decomposition to produce energy ( Guo et al, 2018 ; McIntosh et al, 2019 ; Anagnostopoulos et al, 2022 ; Zhao et al, 2022 ). By molecular docking results, we found that SAN could interact with PPARγ, PPARα and FABP1 , suggesting that SAN can regulate PPAR -mediated lipid metabolism signaling pathway.…”
Section: Discussionmentioning
confidence: 99%